2022
DOI: 10.1021/acscatal.2c03720
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic NiM/C (M = Cu and Mo) Catalysts for the Hydrogen Oxidation Reaction: Deciphering the Role of Unintentional Surface Oxides in the Activity Enhancement

Abstract: Emerging interest in the platinum group metal (PGM)-free electrocatalysts calls for a fundamental understanding of the key factors determining their activity, the latter being critical for the development of efficient catalysts. Ni-based materials show high promises as PGM-free anodes of anion exchange membrane fuel cells (AEMFCs). However, their hydrogen oxidation reaction (HOR) activity can differ by several orders of magnitude, and the factors responsible for this are still being debated. In this work, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
(126 reference statements)
1
2
0
Order By: Relevance
“…ICP-MS results suggest that Ni and Ti dissolutions are negligible in 0.1 M NaOH. Yet, Mo is found to dissolve from the top surface of Ni 4 Mo particles (Supplementary Table S4 ), in good agreement with previously reported Mo dissolution on NiMo alloys 51 54 . The TiO 2 support does not exhibit an inhibitive effect on Mo dissolution.…”
Section: Resultssupporting
confidence: 90%
“…ICP-MS results suggest that Ni and Ti dissolutions are negligible in 0.1 M NaOH. Yet, Mo is found to dissolve from the top surface of Ni 4 Mo particles (Supplementary Table S4 ), in good agreement with previously reported Mo dissolution on NiMo alloys 51 54 . The TiO 2 support does not exhibit an inhibitive effect on Mo dissolution.…”
Section: Resultssupporting
confidence: 90%
“…In the past decade, the alkaline HOR activity of Ni catalysts has been optimized through various elaborate designs such as doping, interface engineering, and alloying. , Among the state-of-the-art Ni-based catalysts, NiMo alloys have been extensively studied and exhibit significantly promoted performance due to the positive regulation from Mo decoration. Serov et al reported the carbon-supported NiMo alloys as the anodic catalysts of AEMFC, which outputted a record power density of 120 mW cm –2 at that time from the single-cell tests. The high activity was attributed to the weakened hydrogen binding energy (HBE) of the Ni sites by adjacent Mo.…”
Section: Introductionmentioning
confidence: 99%
“…Because Co (d7) has a low hydrogen adsorption strength and Mo (d5) has a high hydrogen adsorption strength, the two alloys can draw on each other’s strengths to increase hydrogen adsorption strength and catalytic activity. In addition, binary catalysts consisting of Mo and Co elements have been used as cathodes for hydroelectrolysis. They have demonstrated good catalytic properties due to either crystalline structure modification or electronic formation. Besides, the self-supporting electrode allows for better contact between the catalyst and the reactant on the surface. …”
Section: Introductionmentioning
confidence: 99%